Introduction to credit risk modeling - Bluhm, Christian; Overbeck, Ludger; Wagner, Christoph (Boca Raton, FL : Chapman & Hall/CRC, 2010)
In the first edition of this book the authors focussed on the description of common mathematical approaches to model credit portfolios. They did not change this philosophy for the second edition. Therefore, they left large parts of the book unchanged in its core message but supplemented the exposition with new model developments and with details omitted in the first edition.
Includes bibliographical references and index.
uaj 25/04/13
Loans
Keywords: Credit -- Management -- Mathematical models; Risk management -- Mathematical models